OCCURRENCE OF SALMONELLAS IN FECAL MATTER OF CHILDREN WITH DIARRHEA - OLARTE, JORGE (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1943)
The histology of the liver of a circus elephant is described A new kind of epithelial cell is reported from the walls of the secretory canals
CIENC MEX
Keywords: OCCURRENCE, SALMONELLAS, FECAL, MATTER, CHILDREN, DIARRHEA; CIENCIAS MEDICAS; CIENCIAS CLINICAS; PEDIATRIA